Village Housing Constraints and opportunities in rural England - Gallent, Nick (UCL Press, 2022)
Village Housing explores the housing challenge faced by England's amenity villages, rooted in post-war counter-urbanisation and a rising tide of investment demand for rural homes. It tracks solutions to date and considers what further actions might be taken to increase the equity of housing outcomes and thereby support rural economies and alternate rural futures. Examining past, current and future intervention, the book's authors look firstly at the interwar reliance on landowners to provide tied housing and post-war diversification of responses to rising housing access difficulties, including from the public and third sectors; secondly, at recent responses that are community-led or rely on flexibilities in the planning system; and thirdly, at actions that disrupt established production processes: self-build, low impact development and a re-emergence of council provision. These responses to the village housing challenge are set against a broader backcloth of structural constraint - rooted in a planning-land-tax-finance nexus - and opportunities, through reform, to reduce that constraint. Village Housing makes the case for planning, land and tax reforms that can broader the social inclusivity and diversity of villages, supporting their economic function and allowing them to play their part in post-carbon rural futures. It aims to contribute greater understanding of the village housing problem - framed by the wider cost crisis afflicting advanced economies - and offer glimpses of alternative relationships with planning and land.